THE USE OF AN MGLUR5 ANTAGONIST FOR TREATING OPIOID ANALGESIC TOLERANCE - DOLMETSCH RICHARD CARL ELCIARIO; GOMEZ-MANCILLA BALTAZAR; GASPARINI FABRIZIO (2021)
The invention relates to the use of a mGluR5 antagonist for the treatment of opioid analgesic tolerance associated with chronic opioid use in chronic pain. 本发明涉及mGluR5拮抗剂用于治疗与慢性疼痛中的慢性阿片类物质使用相关联的阿片类物质镇痛耐受性的用途。